Chemical speciation of lead in secondary fly ash using X-ray absorption spectroscopy. (April 2018) - Tian, Shulei; Zhu, Yingcai; Meng, Bangbang; Guan, Jian; Nie, Zhiqiang; Die, Qingqi; Xu, Wei; Yu, Meijuan; Huang, Qifei
Abstract: In this study, fly ash samples were collected from bag houses in a Chinese municipal solid waste incinerator (MSWI) and secondary fly ash (SFA) samples were collected from a high-temperature tubular electric furnace by thermal treatment of MSWI fly ash at 1050, 1100, 1150, 1200, and 1250 °C.We determined the speciation and atomic coordinates of lead in SFA using X-ray absorption spectroscopy (XAS) techniques. The results obtained by X-ray absorption near edge structure (XANES) spectra revealed that the mass fraction of PbO in MSWI fly ash was 57.9% ( w t %) while PbCl2 and PbS were the dominant species in SFA. Extended X-ray absorption fine structure (EXAFS) data analysis indicated the atomic coordinates of Pb were proportional to the weights of PbCl2 and PbS, in good agreement with the XANES spectra. These findings highlight lead evaporation processes in the MSWI fly ash during heat treatment and provide a method for consistent speciation analysis of environmental samples using XAS. Graphical abstract: Image Highlights: XAS and XANES were first used to analysis the speciation of SFAs. PbCl2 and PbS was the main existed speciation of Lead in the SFAs. The concurrent presence of chloride would improve the evaporation of lead. This work would make a possible basis for setting up a unique lead recycling process.